Advanced functional materials : a perspective from theory and experiment - Sanyal, Biplab; Eriksson, Olle. (Amsterdam : Elsevier, 2012)
This book deals with functional materials that are in the frontiers of current materials science and technology research, development and manufacture. The first of its kind, it deals with three classes of materials, (1) magnetic semiconductors, (2) multiferroics, and (3) graphene. Because of the wide popularity of these materials there is a strong need for a book about these materials for graduate students, new researchers in science and technology, as well as experienced scientists and technologists, technology based companies and government institutes for science and technology. The book will provide this broad audience with both theoretical and experimental understanding to help in technological advances in the development of devices and related new technologies based on these very interesting and novel materials. Covers both the theoretical and experimental aspects of advanced functional materials, which are important for use in a number of rapidly developing novel technological devices Includes excellent coverage of three of the leading advanced functional materials. Edited by a leading expert at the forefront of advanced functional materials research.
Includes bibliographical references and index.
Keywords: Materials; Graphene